Analisis Arah Kiblat Masjid Sigi Lamo Kesultanan Ternate - Sitti Nurchalifa Umaternate; Asep Ramdan Hidayat (Jurnal Riset Hukum Keluarga Islam, 2021)
Abstract. Mosques occupy an important position in the life of Muslims, not only in ritual worship, but also in various aspects of Muslim life. The Sultanate of Ternate is one of the four sultanates in North Maluku. Evidence of the existence of the Sultanate of Ternate is the existence of the Sultanate Mosque, one of the oldest and largest Sultanate mosques in the Sultanate of Ternate is Sigi Lamo which keeps a history of Islamic civilization and culture that still stands today. Until now, the mosque is still standing and has become the center of life for Muslims in Ternate, as a reference in fostering customs, culture and religion. The direction of the Qibla which is part of the valid requirements of prayer is an important thing in carrying out prayer services. Sigi Lamo which is a historical mosque, in determining the direction of the Qibla has been established since its inception. The direction of the Qibla of the Sigi Lamo Mosque in the Sultanate of Ternate has not changed since its inception until now, because of the sacredness of the mosque. Therefore, the author wants to examine the accuracy of the direction of the Sigi Lamo Qibla and in view of the fiqh facing the Qibla and the culture of the Ternate people. This study used a qualitative research method with a descriptive analysis approach. The purpose of this study was to determine the accuracy of the Qibla direction of the Sigi Lamo Mosque in the Sultanate of Ternate and its relationship with Fiqh. The results showed that the direction of the Qibla of the Sigi Lamo Mosque in the Sultanate of Ternate deviated from the direction of the Qibla by 20 ° 24'10 "to the south, whereas the direction of the qibla that should have been 290 ° 24'10" (too westward). This deviation occurs because of the opinion of the surrounding community about the sacredness of the mosque building and the direction of the Qibla. Abstrak. Masjid menduduki posisi penting bagi kehidupan umat Islam, tidak hanya dalam ritual ibadah saja, namun juga dalam berbagai aspek kehidupan umat Islam. Kesultanan Ternate adalah salah satu dari empat kesultanan yang berada di Maluku Utara. Bukti dari eksistensinya Kesultanan Ternate ialah masih berdirinya Masjid Kesultanan, salah satu masjid Kesultanan yang tertua dan terbesar di Kesultanan Ternate ialah Sigi Lamo yang menyimpan sejarah peradaban dan kebudayaan Islam yang masih berdiri hingga sekarang. Hingga saat ini masjid tersebut masih kokoh berdiri dan menjadi sentra kehidupan umat Islam di Ternate, seperti menjadi rujukan dalam pembinaan adat, budaya, dan agama. Arah kiblat yang merupakan bagian dari syarat sah Shalat menjadi hal yang penting dalam melaksanakan ibadah shalat. Sigi Lamo yang merupakan masjid yang bersejarah, dalam penentuan arah kiblat telah di tetapkan sejak awal di dirikan. Arah kiblat Masjid Sigi Lamo Kesultanan Ternate sejak awal didirikan hingga saat ini tidak mengalami perubahan, karena kesakralan dari Masjid. Oleh karenanya, penulis ingin meneliti akurasi arah kiblat Sigi lamo serta di tinjau dari fiqh menghadap kiblat serta kebudayaan masyarakat Ternate. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif analisis Tujuan dari penelitian ini adalah untuk mengetahui akurasi arah kiblat Masjid Sigi Lamo Kesultanan Ternate dan hubungannya dengan Fiqh. Hasil penelitian menunjukkan bahwa arah kiblat Masjid Sigi Lamo Kesultanan Ternate menyimpang arah kiblatnya sebesar 20°24'10" ke arah selatan, padahal arah kiblat yang seharusnya adalah 290°24'10" (terlalu ke arah Barat). Penyimpangan tersebut terjadi karena anggapan masyarakat sekitar tentang kesakralan bangunan masjid berikut arah kiblatnya.